FAIRDOMHub: a repository and collaboration environment for sharing systems biology research. Issue Volume 45:Issue D1(2017) (24th November 2016) - Wolstencroft, Katherine; Krebs, Olga; Snoep, Jacky L.; Stanford, Natalie J.; Bacall, Finn; Golebiewski, Martin; Kuzyakiv, Rostyk; Nguyen, Quyen; Owen, Stuart; Soiland-Reyes, Stian; Straszewski, Jakub; van Niekerk, David D.; et al.
Abstract: The FAIRDOMHub is a repository for publishing FAIR (Findable, Accessible, Interoperable and Reusable) Data, Operating procedures and Models (https://fairdomhub.org/ ) for the Systems Biology community. It is a web-accessible repository for storing and sharing systems biology research assets. It enables researchers to organize, share and publish data, models and protocols, interlink them in the context of the systems biology investigations that produced them, and to interrogate them via API interfaces. By using the FAIRDOMHub, researchers can achieve more effective exchange with geographically distributed collaborators during projects, ensure results are sustained and preserved and generate reproducible publications that adhere to the FAIR guiding principles of data stewardship.